2020
DOI: 10.1177/2058739220942335
|View full text |Cite
|
Sign up to set email alerts
|

Anti-proliferative and apoptosis-inducing effects of matricin on human non-small cell lung cancer H1299 cells via MAPK pathway activation

Abstract: Lung cancer in humans is majorly represented by non-small cell lung cancer cells, and there is a constant search for an efficient therapeutic approach. This study aims to find the anti-proliferative and apoptotic effects of matricin on H1299 cells via activation of MAPK pathway. Non-small cell H1299 cells were subjected to viability analysis with MTT assay and anti-proliferation analysis with different concentrations of matricin. Apoptosis was determined with annexin V/propidium iodide (PI) and flow cytometric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…These effects lead to the increase in apoptotic factors and the reduction of metastasis, cellular invasion and anti-apoptotic factors. Illustratively, earlier study demonstrated the potentiality of matricin to significantly exert anti-proliferative and apoptosis-inducing effects in non-small cell lung cancer cells via activation of MAPK pathway [ 61 ]. Additionally, expression of anti-apoptotic proptein Bcl-2 was significantly decreased while the level of pro-apoptosis protein Bax as well as the activity of apoptosis marker enzymes caspase-9, caspase-8 and caspase-3 were significantly increased.…”
Section: Resultsmentioning
confidence: 99%
“…These effects lead to the increase in apoptotic factors and the reduction of metastasis, cellular invasion and anti-apoptotic factors. Illustratively, earlier study demonstrated the potentiality of matricin to significantly exert anti-proliferative and apoptosis-inducing effects in non-small cell lung cancer cells via activation of MAPK pathway [ 61 ]. Additionally, expression of anti-apoptotic proptein Bcl-2 was significantly decreased while the level of pro-apoptosis protein Bax as well as the activity of apoptosis marker enzymes caspase-9, caspase-8 and caspase-3 were significantly increased.…”
Section: Resultsmentioning
confidence: 99%